THEORETICAL ASPECTS OF THE STATE JOINT-STOCK CAPITAL IMPLEMENTATION IN THE DEVELOPMENT OF THE PUBLIC-PRIVATE PARTNERSHIPS - Vaslavskaya, Irina; Koshkina, Irina; Egorova, Larisa (Revista Inclusiones, 2020)
In the modern Russian economy, public and private capital work together to solve national problems based on a public-private partnership. The article discusses the main trends in the development of the public-private partnerships using the example of joint-stock companies with a state participation in catering. The functions and role of the joint-stock capital in the economic realization of the State share ownership are justified in the absence of historical experience of State-business partnership in Russia. The place and function of State joint-stock ownership were considered, on the one hand, in the context of the study of the targeted functions of State property, on the other hand, the specific nature of its functioning as a joint-stock liability was taken into account. It was shown in the article that the main problems in this area are related to the general problems of legal regulation of property and control issues in the economy. The universality of the public-private partnership as a mechanism for the development of the economy is justified, which allows, through the interaction of the state and business, aimed at the development of the whole society, to obtain a large socio-economic effect.